Arabia's fifth-millennium BCE pastoral well cultures: hypotheses on the origins of oasis life - Gebel, Hans Georg K. (Proceedings of the Seminar for Arabian Studies, 2013)
Sepulchral landscapes characterized Arabia's fifth millennium BCE from south-eastern Jordan in the west to Yemen in the east. New evidence from the Qulbān Banī Murra and Rajājil areas shows that these extensive and rather unknown, partly megalithic burial fields were also connected to water management systems. This indicates that they were not only regional centres of commemoration and (tribal?) identity for the mobile pastoral groups benefitting in these mid-Holocene times from moisture episodes on the Arabian Peninsula, but that they also represented meeting places for watering flocks and social transaction. The hydraulic competency and social structures of these well cultures, which used water trough systems, channels, and dams at hydrologically favoured places (high aquifers, seasonal lakes, barraged wadis), may have led to Arabia's earliest oasis socio-economies, a forced adaptation to sedentary life when the climate became colder and drier during the fourth millennium BCE. Depending on their specific ecological conditions, not all regions may have successfully participated in this transition. In parallel, dry areas of the Arabian Peninsula must also have continued to sustain mobile pastoral groups, although witnessing a reduction of their populations. This contribution aims to present the first research hypotheses on such a general potential transition for the Arabian Peninsula, developed on the basis of—and illustrated by—new evidence from south-eastern Jordan and north-western Saudi Arabia.